A efetividade dos códigos de ética empresarial na percepção do executivo brasileiro de empresas nacionais sujeitas à lei Sarbanes-Oxley : uma análise exploratória baseada no modelo de Singh - Manfredi, Claudio Alexandre Ferreira (2013)
Companies seek to create an enabling context in which trust is a predominant element . In 2002, after the well - known corporate governance scandals, the Congress of the United States of America (USA) enacted the Sarbanes - Oxley Act (SOx), in order to protect investors and reestablish the shaken confidence. U.S. public companies were forced to adopt corporate codes of ethics, ensuring maximum effectiveness in preventing frauds committed by their employees, subject to heavy civil and criminal penalties for both companies and their executives. This study aims to assess the effectiveness of the Co rporate Codes of Ethics ( CC E) by the perception of Brazilian employee s of Brazilian national companies subject to comply with S o x . Based on the model described by Singh (2011), 18 independent variables of CCE’ effectiveness were analyzed . The results reve aled that 84.4% of the questionnaire respondents positively evaluated the C CE of their respective companies. But the model of Singh (2011) did not fully reflect the factors identified by him , allowing the proposi tion of a new model of effectiveness of the CCE . Further research should include an analysis of the Brazilian cultural aspects that may impact the effectiveness of the EEC. Case studies regarding the universe of employees of one sole public company should be conducted , aiming to provide a n actual diagnosis of the effectiveness of its code of ethics.